War, diplomacy and the rise of Savoy, 1690-1720 - Storrs, Christopher (Cambridge studies in Italian history and culture., 2000)
This book deals with the crucial relationship between war and state formation in early modern Europe by examining the participation of Savoy in the Nine Years War (1688-97) and the War of the Spanish Succession (1701-14) under Duke Victor Amadeus II.